Bacteria Isolated From Milk of Dairy Cows With and Without Clinical Mastitis in Different Regions of Australia and Their AMR Profiles - Al-harbi, Hulayyil; Ranjbar, Shahab; Moore, Robert J.; Alawneh, John I. (Frontiers in Veterinary Science, 2021)
Mastitis is the most common disease in dairy cattle worldwide. The objectives of this study were to estimate the prevalence of different bacterial species associated with mastitis from dairy herds located in geographically and climatically distinct zones in Australia, and to evaluate the antimicrobial susceptibility of the isolated bacteria. Quarter-level milk samples (n = 419) were collected from 151 mastitis cases and 268 healthy controls originating from 18 dairy herds located in tropical (Northern Queensland), subtropical (Southeast Queensland) and temperate zones (Victoria) between March and June 2019. Milk samples were cultured, and the isolated bacteria were grouped into six groups: Enterobacteriaceae spp.; Streptococcus spp.; Staphylococcus aureus, non-aureus staphylococci (NAS); Bacillus spp.; and Others. Mixed effects conditional logistic regression models were applied to quantify the association between the prevalence of each bacterial group and the herd zone and bulk milk tank somatic cell counts (BMTSCC). Of the 205 isolates, 102 (50%) originated from mastitis cases, and 103 (50%) from controls. Staphylococci were the most prevalent (NAS 32% and S. aureus 11%). Contagious mastitis bacteria were more prevalent in Victoria compared to Queensland dairy herds. NAS species (P < 0.001) were less prevalent in herds with BMTSCC >300,000 cells/mL compared with herds with low BMTSCC ≤150,000 cells/mL. Enterobacteriaceae and Streptococcus spp. groups showed high resistance rates to 1 (51% and 47% respectively) and 2 (11% and 23% respectively) antimicrobials. More than one third of the Enterobacteriaceae (48%) and Others (43%) groups spp. were resistant to at least three antimicrobials. This study provided a unique opportunity to investigate the prevalence of mastitis-associated bacteria in clinical cases and in apparently healthy controls. The findings of this study help inform mastitis control and antimicrobial stewardship programs aimed to reduce the prevalence of mastitis and antimicrobial resistance in dairy herds.